Nickel-Catalyzed Asymmetric Arylation of H-Phosphinates - Zhang, Qing; Cui, Ran-Ran; Zhang, Qing-Wei (Synlett, 2023)
An asymmetric arylation of H-phosphinates with aromatic iodo or bromo compounds, catalyzed by cheap and easily available nickel(II) salts, provides access to P-stereogenic phosphinates. This method features mild reaction conditions and a good functional-group compatibility that includes aniline and phenol derivatives.
Keywords: phosphinates; P-stereogenic centers; phosphinates; nickel catalysis; cross-coupling; asymmetric catalysis